Problem-Based Learning Berbantuan Media Manipulatif untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa Kelas I Madrasah Ibtidaiyah - Muflihah, Nurul; Yusna Devi, Wiwi (LPPI Yayasan Almahmudi bin Dahlan, 2025)
The fundamental issue in early-grade mathematics learning is the students' difficulty in understanding abstract number operations concepts. An initial study at MIN Kota Solok showed that 76.7% of first-grade students failed to solve contextual problems involving addition and subtraction within 1-20, indicating low mathematical problem-solving abilities. This study aims to improve the mathematical problem-solving ability of first-grade students at MIN Kota Solok through the implementation of Problem-Based Learning (PBL) assisted by manipulative media. This research is a Classroom Action Research (CAR) conducted in two cycles, following the Kemmis and McTaggart model. Each cycle consisted of planning, action, observation, and reflection. Data were collected through tests, observation, and documentation. The results showed a significant improvement. The classical mastery percentage increased from 23.3% (pre-cycle) to 63.3% in cycle I and 86.7% in cycle II. The average score also rose from 50.0 (pre-cycle) to 66.0 (cycle I) and 82.0 (cycle II). Observational data indicated an increase in student activity and engagement in the learning process. The integration of the PBL model with manipulative media is effective in enhancing first-grade students' mathematical problem-solving abilities.